MORPHOLOGICAL HI8STOPATHOLOGICAL CHANGES IN SOME LIVER DISEASES IN CATTLE - G. Habasha, F.; Al- Jeddah , M.; M. Al-Darraji‎, A. (The Iraqi Journal of Veterinary Medicine, 1988)
Liver biopsies were taken from (89) cattle slaughtered at modern Baghdad abattoir. Macroscopic examination of livers showed that (28.11%) of cases were infected with chronic fascioliasis, while (1.12%) of livers showed acute fascioliasis and (2.24%) of livers showed chronic fascioliasis with hydatidosis. Hydatid cysts were present in (6.74%) of inspected livers, telangiectasis of the livers found in (3.37%) of cases, focal hepatic necrosis (Saw dust) was observed in (19.1%), liver abscesses constituted (1.12%) and (38.2%) of livers had no significant gross lesions. The diagnosis of liver diseases in cattle using liver biopsy technique was more successful when the lesion was extensively diffuse in the liver.